Dataset Teacher judgement accuracy of technical abilities in primary education - Wammes, Dannie (Utrecht University, 2022)
Raw data and analyses used for
Wammes, D., Slof, B., Schot, W., & Kester, L. (2022). Teacher judgement accuracy of technical abilities in primary education. International Journal of Technology and Design Education, 1-24.
Keywords: Social Sciences - Educational sciences (5.3); Engineering · Primary education · Judgement accuracy · Formative assessment